Evaluation of Total Thyroidectomy for Treatment of Benign Diseases of Thyroid Gland - Cholancheski, Risto; Tolevska, Natasha; Qafjani, Ardit; Vela, Ilir; Kondov, Borislav; Kondov, Goran; Jakupi, Nexhati; Dzikovski, Igor; Kokareva, Anita; Srceva, Mimi; Tolevska, Marija; Kartalov, Andrijan; et al. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The controversy of using total thyroidectomy (TT) in treatment of benign thyroid diseases still remains controversial over the rates of complication, mostly recurrence nerve palsy and hypocalcemia, compared to non-total thyroidectomies. The latest reports in this field of research showed that that the number of complications of TT is decreasing as the skills of surgeons increase. AIM: In this study, we reviewed 209 cases of total thyroidectomies for benign thyroid diseases where such surgery was indicated. The results were evaluated whether they support the previous reports that TT is save method of treatment of diffuse multinodular goiters, Graves’ disease thyroid adenomas with diffuse goiters and thyroiditis. METHODS: Two hundred and nine patients, 36 males and 173 females, medium age 47 (17–77) operated with TT between 2016 and 2018 were included in the evaluation study. We evaluated the: Diagnosis, indications for operation, pre-operative medication administration, laryngeal recurrent nerve palsy, hypocalcemia, hypoparathyroidism, and patohistology findings. The follow-up for hypocalcemia and laryngeal nerve palsy was performed 1 year postoperatively. RESULTS: The age of the patients was between 17 and 77 years, medium-range 47 years old. Of 209 patients, 173 (83%) were female and 36 (17%) male with a gender ratio of 1:4.8 males to females. Diagnoses before surgery were established as follows: Multinodular euthyroid goiter (MNEG) n = 106 (48.80%), multinodular toxic goiter n = 12 (5.74%), Graves’s disease n = 6 (2.87%), adenoma with multinodular goiter n = 73 (34.92%), and n = 16 (7.65%) patients with thyroiditis. Recurrence laryngeal nerve palsy (RLNP) occurred in 6 patients (2.87%), temporary within 3 months after the operation in 4 patients (1.92%) and permanent palsy within 6 months and more after an operation in 2 patients (0.95%). Voice hoarseness immediately and within 1 month after the operation was registered in 32 patients (15.3%). RLNP and hoarseness were registered mostly in patients with pre-operative problems, mostly with extra big MNEG. One of the permanent injuries of RLN was bilateral and all others were one sided. All patients were operated with normal pre-operative vocal cord movement findings. Post-operative hypocalcemia was registered in 35 patients (16.74%). Temporary nonsignificant hypocalcemia in 10 (4.78%), temporary significant hypocalcemia in 17 (8.13%), temporary severe hypocalcemia in 6 patients (2.87%), and permanent hypocalcemia in 2 patients (0.95%). CONCLUSION: Many studies have shown that the rate of complications is almost even for TT and NTT done for benign and malignant diseases of thyroid gland. Our data have shown that the risk of post-operative complications with TT is proportional to the number of complicated pre-operative findings of benign thyroid glands.